PEMBELAJARAN TAUHID BERBASIS LINGKUNGAN DI SMP IT ALAM NURUL ISLAM YOGYAKARTA - Hamdhan Djainudin; Sangkot Sirait (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
As we know, environmental damage in Indonesia and natural balance has been disrupted. Religion, especially Islam actually have a clear concept of saving the environment. Islam is a religion that believes that the environment is an integral part of person’s faith in Allah. In this reseacrh, researchers used Field Research that are descriptive qualitative, at SMP IT Alam “Nurul Islam” Yogyakarta. From the research, it was found that the effort in the Tauhid based learning environment at SMP IT Alam Nurul Islam Yogyakarta, that is: 1. Learning in the classroom, 2. learning field or learning outside the classroom. With the aim for the creation of social sensitivity and love and respect for the environment and natural as high.